1992
DOI: 10.1182/blood.v79.1.45.45
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids downregulate gene expression of GM-CSF, NAP-1/IL-8, and IL-6, but not of M-CSF in human fibroblasts

Abstract: Cytokines such as granulocyte-macrophage colony-stimulating factor (GM- CSF), macrophage-CSF (M-CSF), neutrophil-activating peptide- 1/interleukin-8 (NAP-1/IL-8), and interleukin-6 (IL-6) are pivotal in the regulation of hematopoiesis and immune responses. In mesenchymal cells, their expression is induced by tumor necrosis factor alpha (TNF) and other agents. We now show that, while induction of cytokine expression by TNF in human lung fibroblasts was parallel, glucocorticoid hormones differentially affected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(79 citation statements)
references
References 27 publications
4
75
0
Order By: Relevance
“…activator protein-1 (AP-1) and nuclear factor kappa B (NF-kB)] that are required for the transcription of proinflammatory cytokines, including IL2, INFG and CSF2 [30,32]. Furthermore, glucocorticoids are reported to inhibit cytokine secretion by reducing mRNA stability [33], and by suppressing the cytokine-producing cell populations [34]. We observed that the two patients with ongoing rejection therapy with methylprednisolone (500-125 mg) presented significantly reduced E 0 , as well as strong inhibition of cytokines after dosing (RGE 1.5% and 11.1%).…”
Section: Discussionmentioning
confidence: 99%
“…activator protein-1 (AP-1) and nuclear factor kappa B (NF-kB)] that are required for the transcription of proinflammatory cytokines, including IL2, INFG and CSF2 [30,32]. Furthermore, glucocorticoids are reported to inhibit cytokine secretion by reducing mRNA stability [33], and by suppressing the cytokine-producing cell populations [34]. We observed that the two patients with ongoing rejection therapy with methylprednisolone (500-125 mg) presented significantly reduced E 0 , as well as strong inhibition of cytokines after dosing (RGE 1.5% and 11.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary fibroblasts have now been recognized as an active participant during inflammatory processes in the lung, playing a specialized role in the recruitment and regulation of immune cells that infiltrate the interstitial space. Through their regulatory mechanisms, lung fibroblasts generate many kinds of chemokines and cytokines, including IL-8, eotaxin 1, MCP-1, MIP-1a, RANTES, and GM-CSF, upon activation with inflammatory stimulants [1][2][3]. IL-8 (CXCL8) is one of the major chemokines with neutrophil chemotactic activity [4], and is produced by a variety of cells including lung fibroblasts activated with various stimulants [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…While this cellular demargination can also be a marker of bacterial infection, the latter is typically manifested by a large increase in total leukocyte count (Busch et al 1998;Nathan 2006). Apart from the effects on cell numbers, the release of glucocorticoids in response to acute stressors has also been associated with an inhibition of IL-6 responses to endotoxins (Ahmed & Ivashkiv 2000;Akira & Kishimot 1992;Tobler et al 1992;Waage et al 1990;Zitnik et al 1994). This inhibition of cellular reactions is distinct from the in vivo increase in IL-6 secretion from many nonlymphoid tissues, which has described as the proinflammatory bias seen after sustained psychological stress and sometimes in glucocorticoid resistance states, such as posttraumatic stress disorder (Kiecolt-Glaser et al 2003;Lutgendorf et al 1999;Maes et al 1998;Miller et al 2002).…”
Section: Discussionmentioning
confidence: 99%